Quantitative assessment of morphological traits of planktonic bacterial aggregates. (1st January 2021) - Espeso, David R.; Martínez-García, Esteban; de Lorenzo, Víctor
HIGHLIGHTS: A methodology is proposed to quantify morphological diversity of bacterial flocs. The system was tested with bacterial cells attached through artificial adhesins. The method delivers quantifiers to explore variables of cell aggregation processes. Abstract: The efficiency of multi-strain planktonic flocs of bacteria as biocatalytic agents in aqueous media depends to a considerable extent on their three-dimensional aggregation patterns. Yet, numerical methodologies for full characterization of such heterogeneous biomass structures are largely missing. In this work we present a descriptive methodology for quantitatively portraying and identifying suspended cell clumps formed by planktonic bacteria. In order to benchmark the procedure, we tackled the behavior of cells of the environmental and biotechnologically robust species Pseudomonas putida whose surfaces were decorated with genetically encoded adhesins. Upon induction, such adhesins promoted specific inter-bacterial attachment leading to controllable and tractable floc formation in suspension. Microscopy and flow cytometry data were then gathered and further analyzed by means of a distinct metric set. Applying these parameters permitted creating comparable clumping footprints for every sample at both single-cell and population level. The hereby described approach provides a rigorous frame for following the assembly and organization of complex microbial communities as planktonic flocs.